An Investigation into The Relationships and Discrepancies between UK Consumers’ Materialistic Values, Their Environmental Attitudes, and Their Consumer Behaviour - West, Laura (2013)
This study examines the relationship between consumers’ materialistic values and their support for the New Environmental Paradigm (NEP), which measures the extent to which individuals perceive humans as separate or an integrated part of the rest of the natural environment. The research found that although many of the participants show a strong support for the NEP, the strength of many of the individuals’ materialistic values, and the extent to which these values are promoted and reinforced throughout society, leads to the dominance of consumers’ materialistic values over their environmental concerns, and as a result these materialistic values act as a critical barrier to sustainable consumer behaviour. Furthermore, the results found that many of the more materialistic consumers within the sample had lower perceptions of their consumer behaviour as being environmentally significant. This relationship is suggested to be a denial mechanism which consumers with strong materialistic values may use in order to reduce potential feelings of psychological dissonance which may arise as a result of their excessive consumption and acting out of alignment with their environmental beliefs. It is subsequently suggested that if the transition to a sustainable consumer society is to occur, it is essential to change both the underlying forces within society which perpetuate consumers’ materialistic values, but it is also necessary to change consumer values in order to bring about the transformation of society.